Emotion regulation strategies on depression through a problematic use of technology: toward an explanation of the association between depressive symptomatology and internet addiction - Hernández, Cristóbal (2019)
Depression has been reliably associated in the past with uncontrolled use of the Internet regardless of its consequences, a phenomenon commonly referred to as Internet addiction. However, less attention has been afforded to explaining this association. The present study aims to provide a potential explanation based on current theoretical accounts of emotion regulation and the problematic use of the Internet. To achieve this goal, this dissertation comprises three articles. The first discusses a transcultural adaptation of the most psychometrically evaluated measure of Internet addiction and a test of its psychometric properties on an adult sample from Chile. Next, using a sample of Chilean high school students, a cross-sectional test of two potential mechanisms linking depressive symptomatology and Internet addiction investigates the possibility of being cognitively absorbed on the Internet (referred to as flow experiences online) and using the Internet to postpone unpleasant tasks (referred to as Internet procrastination). The final article analyzed data from the follow-up measurements of the adolescent sample to provide a longitudinal explanation of the association between depressive symptomatology and Internet addiction for those using the Internet to disconnect from life situations, that is, using the Internet as a proxy for an attentional deployment emotion regulation strategy. Taken together, results suggest that the inflexible use of the Internet to regulate emotional experiences may influence the development of Internet addiction based on a negative affective state such as the presence of depressive symptomatology. A possible vicious circle is theoretically discussed, together with the study limitations and potential implications for both clinical practice and future research efforts. It is hoped that the present study sheds light on the mechanisms linking the technologically mediated context with adolescent affective processes.